Reporting of Medical Errors in Autopsied Cases - Sah, Bikash; Yadav, B. N.; Jha, Shivendra; Ayer, Ashok; Yadav, Ajay Kumar (Journal of Nepal Health Research Council, 2017)
This report describes the cases autopsied at B. P. Koirala Institute of Health Sciences- Nepal, during the period of two years in which the treatment provided falls below the accepted standard practice causing the death of the patient. Postmortem examination provides an opportunity to find out the actual cause of death in which the cause of death is suspicious. Sometimes the cause of death found through postmortem examination is different from the clinical cause of death. The autopsy finding on the cause of death will help doctors even to think about unusual conditions that lead to death and hence apply preventive measures for those unusual conditions. The cause of medical error is not always due to the doctor’s mistake, but sometimes also due to the obsolete hospital protocol. The autopsy reporting of medical errors can be used to identify lacunae in hospital protocols, problem-prone clinical processes and suggest interventions that may reduce negligence.